Effects of Al2O3 Type on Activity of Al2O3-Supported Rh Catalysts in Single-Walled Carbon Nanotubes Growth by CVD. (16th January 2017) - Kiribayashi, Hoshimitsu; Fujii, Takayuki; Saida, Takahiro; Naritsuka, Shigeya; Maruyama, Takahiro
ABSTRACT: We carried out single-walled carbon nanotube (SWCNT) growth using a Rh catalyst on Al2 O3 buffer layers that were prepared by three different methods based on electron beam (EB) evaporation: native oxidation of Al layer deposited by EB ([EB(Al)+NO]-Al2 O3 layer); thermal oxidation of Al layer deposited by EB ([EB(Al)+TO]-Al2 O3 layer); EB deposition of Al2 O3 layer ([EB(Al2 O3 )]-Al2 O3 layer). SWCNT yield was the largest for the [EB(Al2 O3 )]-Al2 O3 layer, while SWCNTs were not grown on the [EB(Al)+NO]- Al2 O3 layer. Transmission electron spectroscopy showed that most of Rh particle sizes were distributed between 1.0 and 2.6 nm on the [EB(Al)+NO]- Al2 O3 and [EB(Al2 O3 )]- Al2 O3 layers, while they were distributed between 1.8 and 4.2 nm on the [EB(Al)+TO]- Al2 O3 layer. This result indicates that surface migration of Rh catalysts was suppressed on the [EB(Al2 O3 )]- Al2 O3 layer, resulting in the largest SWCNT yield. On the other hand, enlargement of Rh catalyst particles occurred on the [EB(Al)+TO]- Al2 O3 layer, leading to the reduction of SWCNT yield. Taking into account our previous study, inward diffusion of Rh catalysts into the Al2 O3 buffer layer inhibited SWCNT growth on the [EB(Al)+NO]- Al2 O3 layer, although enlargement of Rh particle size was suppressed. We also carried out ultra-violet photoemission measurements for Rh catalysts on the [EB(Al)+TO]- Al2 O3 and [EB(Al2 O3 )]- Al2 O3 layers and investigated the electronic states of Rh catalysts on them.